Inculcating knowledge sharing behavior in organization: roles of intrinsic and extrinsic motivations - Mohd Rasdi, Roziah; Tangaraja, Gangeswary (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Despite the importance of knowledge sharing practice, studies indicated that some employees are still reluctant to share knowledge with other colleagues. This have led to inefficiency and fragmentation of services and at times to the extent of service breakdown in organization. Past studies revealed that the major enablers of employee’s knowledge sharing behavior were associated to motivational factors. However, few researches have examined the effect of motivational factors especially intrinsic motivation factors on knowledge sharing. Thus, this study aims to investigate the influence of motivational factors (intrinsic and extrinsic) on employees’ knowledge sharing behavior. Surveys were designed based on established instruments and yielded 231 response from administrators of various managerial grades. The study found that intrinsic motivation factor is an important factor to encourage the development of affective commitment. Administrators who are motivated and committed were most likely to influence knowledge sharing behavior in organization. The conclusion and implications for research and practice are highlighted.